2015
DOI: 10.1007/s00261-015-0352-9
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral artery on contrast-enhanced computed tomography imaging: differentiating intrahepatic cholangiocarcinoma from poorly differentiated hepatocellular carcinoma

Abstract: The presence of an intratumoral artery in the arterial phase on contrast-enhanced dynamic CT was a predictable finding for ICC, and the presence of a washout pattern was a predictable finding for p-HCC, differentiating between ICC and p-HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…IMCC usually have an appearance of capsule retraction. Some researchers thought scirrhous stroma of ICC was related to the imaging of capsular retraction ( 19 ). Resembling the classic findings of IMCC in noncirrhotic liver, bile duct dilatation is also a characteristic of IMCC in cirrhotic liver, because IMCC arises from the ductular epithelium of the biliary tree and regularly accompanies with bile duct wall infiltration leading to bile ducts stricture or blocking while the adjacent bile ducts dilatate.…”
Section: Discussionmentioning
confidence: 99%
“…IMCC usually have an appearance of capsule retraction. Some researchers thought scirrhous stroma of ICC was related to the imaging of capsular retraction ( 19 ). Resembling the classic findings of IMCC in noncirrhotic liver, bile duct dilatation is also a characteristic of IMCC in cirrhotic liver, because IMCC arises from the ductular epithelium of the biliary tree and regularly accompanies with bile duct wall infiltration leading to bile ducts stricture or blocking while the adjacent bile ducts dilatate.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic utility of the enhancement pattern on multiphasic contrast-enhanced CT has been previously reported for malignant hepatic tumors, renal cell carcinomas, small bowel neoplasms, and lung cancer (10)(11)(12)(13). In a recent article (13), Fukuma et al demonstrated the enhancement pattern of 48 squamous cell carcinomas, and the average HU was 33.94 HU in the unenhanced, 75.40 HU in the early, and 92.01 HU in the late phase.…”
Section: Discussionmentioning
confidence: 93%
“…RevIBS = NorIBS random p y (10) Most equations and notation meanings here are consistent with CCNN [21]. NorIBS represents the normalized IBS whose value lies in a narrow range between 0 and 1.…”
Section: ) Disibsmentioning
confidence: 96%
“…Tsunematsu et al [10] used the Chi square test as well as the non-parametric Mann-Whitney U test which were common feature-selection methods to analysis the preselected features, 14 clinical characteristics and some CT imaging features. The logistic regression analysis was applied to find the best features to distinguish between ICC and HCC.…”
Section: Introductionmentioning
confidence: 99%